2007
DOI: 10.1007/s11250-007-9014-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation of growth of Kenya Boran cattle using random regression models

Abstract: Data consisting of 18 884 weight records collected from 1273 Boran cattle from birth to 24 months of age were used to estimate covariance functions and genetic parameters for growth of Boran cattle using random regression (RR) models under a situation of small herd size and inconsistent recording. The RR model fitted quadratic Legendre polynomials of age at recording for additive genetic and permanent environmental effects. Genetic variance increased from birth, reaching an asymptotic value at 455 days and was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…In such cases, random regression models (RRM) would be more robust than conventional models in evaluation of piglet growth performance (Meyer & Hill, 1997;Huisman et al, 2002). Wasike et al (2007) evaluated growth of Kenya Boran cattle using RRM and concluded that RRM have potential for modelling growth, notwithstanding conditions of small herd sizes and inconsistent recording. Future research should explore the use of RRM in genetic evaluation of pig growth data.…”
Section: Resultsmentioning
confidence: 99%
“…In such cases, random regression models (RRM) would be more robust than conventional models in evaluation of piglet growth performance (Meyer & Hill, 1997;Huisman et al, 2002). Wasike et al (2007) evaluated growth of Kenya Boran cattle using RRM and concluded that RRM have potential for modelling growth, notwithstanding conditions of small herd sizes and inconsistent recording. Future research should explore the use of RRM in genetic evaluation of pig growth data.…”
Section: Resultsmentioning
confidence: 99%
“…The set of selection criteria and information sources applied obtained a correlation of around 0.14 to the breeding objective traits targeted. Investigation of genetic and phenotypic correlation between Boran cattle traits could allow for optimal identification of sound selection criteria to match the targeted breeding objectives and yield higher selection accuracies (Wasike et al 2007 To choose an optimum breeding programme that will maximise productivity in selecting a set of objective traits and selection criteria while maintaining genetic progress requires more than just an analysis of individual genetic gains. A combination of genetic and economic evaluation is therefore essential.…”
Section: Genetic Response In Individual Breeding Objective Traitsmentioning
confidence: 99%